THE ROLE OF EDUCATIONAL SUPERVISION IN IMPROVING TEACHER COMPETENCY AND LEARNING QUALITY AT PALUMBONSARI STATE PRIMARY SCHOOL 1 - Fajar Hadiansyah, Chairil (Program Studi Manajemen Pendidikan Islam, 2024)
This research aims to study how educational supervision can help improve the quality of learning in elementary schools. This supervision is carried out to support the development of teacher abilities and ensure quality education. This research used a qualitative approach at SDN Palumbosari I, involving the school principal and teachers as data sources. Research procedures include observations of the school principal's work culture and interviews regarding teacher performance. The research results show that supervision, both administrative and academic, has a major influence on the management, planning and evaluation of learning carried out by teachers. Supervision also helps develop teacher professionalism through training and useful feedback. However, there are several challenges in implementing supervision, such as limited teacher knowledge, lack of creativity, and limited supervision time. Therefore, it is very important to build a more effective supervision system, which involves collaboration between school principals, teachers and supervisors, in order to improve the quality of education in a sustainable manner.